Generalized Predictive Model of Estimation of Inhibition of Muscarinic Receptors M1-M5 - Mikurova, A.V.; Skvortsov, V.S.; Grigoryev, V.V. (Biomedical Chemistry: Research and Methods, 2020)
A general predictive model for assessing the inhibition constant (Ki) value of human acetylcholine muscarinic receptors M1-M5 by potential ligands has been constructed. We used information on the three-dimensional structure of human M1, M2, M4, and M5 receptors, as well as a model of the M3 receptor constructed according to homology based on the structure of the rat M3 receptor. A set of complexes of known inhibitors with the target receptor constructed by means of molecular docking, was selected using an additional option: the coincidence of the spatial position of 4 pharmacophore points of a tested inhibitor and tiotropium, for which the position in the crystal structure was known. For five types of M receptors 199 complexes with known Ki values were selected. Based on the data obtained during molecular dynamics simulation of these complexes by means of the MM-PBSA/MM-GBSA methods, their energy characteristics were calculated. They were used as independent variables in linear regression equations for pKi value prediction. The R2 prediction for the generalized equation was 0.7, and the mean prediction error was 0.55 logarithmic units with a range for pKi=4.7.